2020
DOI: 10.20517/2574-1225.2019.48
|View full text |Cite
|
Sign up to set email alerts
|

Robotic lobectomy costs and quality of life

Abstract: The surgical approach for lobectomy has changed over time with recent data demonstrating that the majority are performed using a minimally invasive approach. While the use of the robotic platform for pulmonary resection has been shown to have acceptable clinical outcomes, cost and quality of life need to be considered when starting a robotic lobectomy program. In this review, we evaluate the literature on cost of robotic lobectomy and quality of life. The results suggest that early experience in a robotic lobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Thus, treating a disadvantaged population is more expensive which adds another disadvantage for this population [170]. Developing a robotic thoracic program is also associated with higher hospitals costs compared to VATS and open approaches [109,[171][172][173][174]. Nevertheless, these additional costs eventually are smoothed out with the use of the robot and are no longer significant [173].…”
Section: Providing Adequate Cares For Allmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, treating a disadvantaged population is more expensive which adds another disadvantage for this population [170]. Developing a robotic thoracic program is also associated with higher hospitals costs compared to VATS and open approaches [109,[171][172][173][174]. Nevertheless, these additional costs eventually are smoothed out with the use of the robot and are no longer significant [173].…”
Section: Providing Adequate Cares For Allmentioning
confidence: 99%
“…Developing a robotic thoracic program is also associated with higher hospitals costs compared to VATS and open approaches [109,[171][172][173][174]. Nevertheless, these additional costs eventually are smoothed out with the use of the robot and are no longer significant [173]. Nevertheless, an ERAS program and a VATS minimally invasive surgery, lead to an overall reduction in the costs of surgical treatments, by reducing adverse post-operative events, complications and reducing hospital length of stay [38,175,176].…”
Section: Providing Adequate Cares For Allmentioning
confidence: 99%
“…The implementation of robot-assisted thoracic surgery for the treatment of NSCLC has dramatically increased over the last decade. However, widespread debate regarding its overall efficacy when compared to VATS continues (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines in robot-assisted thoracic surgery versus video-assisted thoracic surgery in terms of clinical outcomes and cost (4)(5)(6)(7)(8)(9)(10). Several early studies have suggested that the VATS approach is associated with lesser release of cytokines and pro-inflammatory mediators, and that may be responsible for many of the benefits of minimally invasive thoracic surgery over open thoracotomy (11)(12)(13).…”
Section: Original Articlementioning
confidence: 99%
“…However, a number of studies have studied the hospital cost and clinical effectiveness of robotic versus thoracoscopic and open lobectomy. Nishimura reviewed the literature for the cost of robotic lobectomy [72] . Nine of the 18 published articles compared the cost of robotic lobectomy with VATS alone.…”
Section: Discussionmentioning
confidence: 99%